MENINGKATKAN KUALITAS PENDIDIKAN: PELATIHAN MENULIS BUKU MONOGRAF BAGI MAHASISWA ANGKATAN 2021 PGSD UNMUL - Fauzi, Muhammad Sukron; Cahyono, Didik; Naheria, Naheria; Cahyaningrum, Gyta Krisdiana; Sukriadi, Sukriadi; Arafah, Andi Asrafiani (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Monograph writing is an important skill for final year students of the Elementary School Teacher Education Study Program (PGSD) to complete their final project and contribute to the science of education. However, many PGSD students do not have sufficient skills in writing monographs according to academic standards. Therefore, this training aims to improve the ability of PGSD Unmul students in writing quality monographs with a practical and theoretical approach. This training was attended by 40 final year students of PGSD Unmul. Before the training, an initial test was carried out to measure students' understanding in writing monographs, including writing techniques, argument preparation, and the use of appropriate references. The results of the initial test showed that only 30% of students had understood the basics of monograph writing, while the rest still had difficulty in compiling systematic scientific writing. After the training, students take a final test to evaluate their skill improvement. As a result, 80% of participants showed a better understanding of monograph writing, especially in structuring arguments and using references appropriately. This training is expected to help PGSD Unmul students complete their final projects with better quality and enrich their scientific writing skills according to the needs of the world of education. In addition, the improved skills are expected to enrich the references and teaching materials used by lecturers at PGSD, as well as improve the quality of education at the elementary level.